Teachers’ Financial Literacy - Németh, Erzsébet; Béres, Dániel; Huzdik, Katalin; Deák-Zsótér, Boglárka; Mészáros, Aranka (Public Finance Quarterly, 2022)
The aim of the research is to explore the financial knowledge, attitudes, confidence, behaviour and motivations of teachers (N=752) teaching different subjects. The survey is particularly important because their knowledge, attitudes, and behaviours affect the financial awareness of the students they teach. The results indicate a higher level of financial literacy than assumed, revealing that teachers have a higher level of financial literacy than students in higher education. 86% of those surveyed have savings in addition to bank deposits, such as government bonds and other, more complex forms of savings, indicating a high level of financial awareness and inclusion. Teachers highly value their own financial literacy, and similar to those studying in higher education, are risk averse. Their vast majority consider the development of financial literacy in schools important. Financial literacy trainings have a measurably positive effect on the level of knowledge of the participants. Based on the results of the research, it is worthwhile to shape the curricula and the requirements based on the financial awareness and motivation of the teachers.